The Impact of Transformational Leadership on Democratic Party - Herzaky Mahendra Putra; Fendy Suhariadi; Teofilus Teofilus (Journal of Governance, 2022)
This study focuses on analyzing the impact of transformational leadership on the intention to stay, as mediated through commitment. This study focuses on transformational leadership at the top level management in Democratic Party that currently led by Agus Harimurti Yudhoyono. This study employs quantitative methods with estimating techniques based on Structural Equation Modeling (SEM). The primary data used are collected by random sampling from Democratic Party management at the central (DPP) and regional (DPP/DPC) levels. The total number of participants in this study was 304. The stages of data analysis include preliminary analysis, which includes construct validity and reliability, a goodness of fit test, and parameter estimate based on a research model in which transformational leadership is an independent variable, intention to stay is an independent variable, and commitment (commitment) is a mediating variable. The findings indicate that transformational leadership has a positive and significant impact on commitment and that commitment positively influences respondents’ intention to stay with the organization. This demonstrates the significance of transformational leadership in fostering the longevity of political parties due to its ability to improve members' willingness to stay and contribute to the organization. In the framework of political party organizations, idealized influence and inspirational motivation are the most significant roles of transformative leadership.